ANALISIS STRUKTUR BELANJA THE ISLAMIC SCHOOLS OF VICTORIA TAHUN 2024 - Anggri Miftahul Jannah; Atik Shaimah Rabiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the expenditure structure of The Islamic Schools of Victoria (Al-Taqwa College) in 2024. Educational expenditure is an important aspect of financial management because it reflects institutional priorities in allocating resources to support the achievement of educational goals. This study employed a descriptive quantitative approach using secondary data obtained from the Audited Financial Report Year Ended 31 December 2024 of The Islamic Schools of Victoria. Data were analyzed through identification of the proportion of each expenditure component to total expenditure. The findings reveal that personnel expenses constituted the largest expenditure component, amounting to AUD 33,634,978 or 68.25% of total expenditure, followed by depreciation and amortization expenses amounting to AUD 8,299,363 or 16.84%, educational expenses amounting to AUD 1,973,798 (4.01%), property expenses amounting to AUD 1,717,353 (3.48%), finance cost amounting to AUD 654,012 (1.33%), and other expenses amounting to AUD 2,997,902 (6.09%). The expenditure pattern indicates that the institution prioritizes human resource development and maintenance of educational assets as the main strategy in supporting the quality of educational services. This expenditure structure reflects the institution's commitment to long-term investment in educators and learning facilities.